Closing the Mismatch: Encouraging Jobseekers to Reskill for Shortage Occupations - Elisabeth Leduc; Ilan Tojerow (Institute of Labor Economics (IZA), 2025)
We partner with a Public Employment Service to examine whether jobseekers can be encouraged to reskill for shortage occupations. In a large-scale field experiment involving 100,000 recently unemployed individuals, we provide information on shortage occupations and related training opportunities. The intervention increased participation in transversal training courses by 6%, but did not boost enrolment in occupational training for shortage jobs. Jobseekers also shifted their search towards high-demand occupations, yet employment remained unchanged. These findings suggest that while low-cost informational interventions can influence job search and training behaviour, different approaches are likely needed to drive substantial reskilling among jobseekers.
Keywords: J24; J62; J68; 330; Labour shortages; Training; Job search; RCT; Unemployment